DEVELOPMENT OF SCIENCE INTERACTIVE E-MODULES FOR MIDDLE SCHOOLS INTEGRATED WITH AL-QUR'AN VALUES - Yeni, Annisa Fitri; Diliarosta, Skunda; Yanto, Febri (Department of Science Education, 2025)
The application of learning to the Kurikulum Merdeka such as the Pancasila Student Profile has one aspect of achievement in the learning framework, one of which is the dimension of trust, piety to God Almighty and Good character. Kurikulum Merdeka learning frees teachers to use technology in carrying out the learning process. Based on this, research was conducted with the aim of producing valid and practical E-Modules. The type of research used Research and Development (R&D) and uses the ADDIE model using three stages of the model. The validity test of the Interactive E-Module is carried out by the validator and the practicality test is carried out by the science teacher and students. The instrument used was a questionnaire in the form of validity and practicality sheets. The results of the validity test obtained an average value of 0.92 with a very high category. The results of the practicality test by the teacher showed a value of 0.96, by students it was 0.90 in the very high category. It can be concluded that the development of the Science Interactive E-Module for Integrated Middle School Al-Qur'an Values ​​has a level of validity and practicality with a very high category.